2021
DOI: 10.4102/sajid.v36i1.223
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of neonates with Carbapenem-resistant Enterobacteriaceae infections at the King Edward VIII Hospital’s neonatal unit, Durban, South Africa

Abstract: Conclusion:Neonates developed CRE much earlier than previously reported. Invasive procedures on admission carry an associated higher risk for developing CRE, more than the length of stay as previously stipulated. Prevalence of CRE seems to be high in middle-income countries with higher mortality. Thus, strict infection prevention and control (IPC) measures during admission and during the first weeks of life can decrease the incidence and outcome of CRE-related mortality and morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Patient demographics for the cohort were similar to those described in the literature: prematurity, low birthweight, previous NICU admission and the need for invasive and/or non-invasive ventilation. 7 , 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient demographics for the cohort were similar to those described in the literature: prematurity, low birthweight, previous NICU admission and the need for invasive and/or non-invasive ventilation. 7 , 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…Median age of presentation was 14 days in a Gauteng neonatal unit looking at multidrug-resistant Enterobacterales (MDRE), including CRE and 10.5 days in a KwaZulu-Natal study on CRE-infected neonates. 7 , 27 Carbapenem-resistant Enterobacterales infection should therefore be considered in at-risk neonates with long hospital stays and among those with HAI episodes not responding to initial antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli, K. pneumoniae , and Enterobacter cloacae are the major isolates of carbapenem-resistant Enterobacterales (CRE), which cause high morbidity and mortality rates and exhibit worldwide prevalence. 31 , 32 In K. pneumoniae , the rates of resistance to ertapenem and imipenem were severe, at 37.9% and 39.4%, respectively. However, it is encouraging to note that E. coli and Enterobacter cloacae remained highly susceptible to carbapenems.…”
Section: Discussionmentioning
confidence: 99%
“…Shaw et al revealed that isolated Staphylococcus and Klebsiella were the most frequently involved pathogens [37]. There are other studies with similar positive blood culture reports [38][39][40]. Some studies mentioned above, however, showed a higher incidence of the gram-negative organism [38,[40][41][42].…”
Section: Discussionmentioning
confidence: 99%